2018
DOI: 10.1007/s12288-018-0978-1
|View full text |Cite
|
Sign up to set email alerts
|

MYD88 and CXCR4 Mutation Profiling in Lymphoplasmacytic Lymphoma/Waldenstrom’s Macroglobulinaemia

Abstract: Recurrent mutations affecting MYD88 and CXCR4 gene nowadays form the basis for the diagnosis, risk stratification and use of inhibitors targeting these signalling pathways in LPL/WM which are rare B cell neoplasms. MYD88 L265P mutation analysis was performed on 33 cases of LPL/WM by AS-PCR (positivity-84.8%, n = 28/33) and by Sanger sequencing (positivity-39.3%, n = 13/33). We had only two cases with CXCR4 nonsense (NS) mutation (p.S338*) using Sanger sequencing. MYD88 (L265P) mutation detection by AS-PCR can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Unfortunately, the analysis of the genomic profile of CXCR4 is not routinely performed in clinics for LPL/WM patients. Importantly, the sensitivity of the used sequencing technique (allele-specific polymerase chain, Sanger, or whole-genome sequencing) and the nature of the analyzed sample (CD19-positive selected lymphocytes or whole BM) represent the most important issues in defining the mutational status of CXCR4 [152,171]. Therefore, universal guidelines are required to standardize the analysis and bring CXCR4 genomic profiling into clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the analysis of the genomic profile of CXCR4 is not routinely performed in clinics for LPL/WM patients. Importantly, the sensitivity of the used sequencing technique (allele-specific polymerase chain, Sanger, or whole-genome sequencing) and the nature of the analyzed sample (CD19-positive selected lymphocytes or whole BM) represent the most important issues in defining the mutational status of CXCR4 [152,171]. Therefore, universal guidelines are required to standardize the analysis and bring CXCR4 genomic profiling into clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant CXCR4 also aids in the adhesion of B-lymphocytes to the bone marrow stroma resulting in the hypercellular, plasmacytic bone marrow of WM. 9 , 11 - 13 …”
Section: Discussionmentioning
confidence: 99%
“…The mutant CXCR4 also aids in the adhesion of B-lymphocytes to the bone marrow stroma resulting in the hypercellular, plasmacytic bone marrow of WM. 9,[11][12][13] WM has an incidence of approximately 3 cases per one million people per year. About 1400 new cases are diagnosed in the United States per year, comprising of 2% of all cases of non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…CD20 demonstrated that the lymphoma comprised approximately 70-80% of the marrow cellularity while CD138 demonstrated a substantial plasma cell compo-approximately 90% of LPL or WM have MYD88 L265P mutations [1]. Mutations in CXCR4, and ARID1A have also been described [6][7][8]. The diagnosis of LPL is mainly based on histopathologic evaluation of involved tissues, immunophenotypic studies and exclusion of other small B cell lymphoid neoplasms with plasmacytic differentiation.…”
Section: Case Reportmentioning
confidence: 99%